Building the case for biofortification: Measuring and maximizing impact in the HarvestPlus program - Johnson, Nancy L.; Asare-Marfo, Dorene; Zeller, Manfred; Birol, Ekin (African Journal of Food, Agriculture, Nutrition and Development, 2017)
This paper describes the research and related activities that HarvestPlus undertook at each stage of the research process—discovery, proof of concept, delivery at scale—to establish and continuously strengthen the evidence base for program impact. Structured around the program’s theory of change, the evidence base includes estimates of the magnitude of potential impacts on key development outcomes as well as support for key assumptions that underlie outcomes along the impact pathway from release of biofortified varieties through adoption by farmers, consumption by consumers, and ultimately, to improved nutritional status. The HarvestPlus experience has important lessons for research for development (R4D) programs, many of which struggle to demonstrate progress towards outcomes and impacts throughout the research process.